Designing effective partnerships for waste-to-resource initiatives: Lessons learned from developing countries. Issue 12 (December 2015) - Storey, Donovan; Santucci, Lorenzo; Fraser, Rowan; Aleluia, Joao; Chomchuen, Laksiri
Cities in developing countries across Asia-Pacific are struggling to effectively manage municipal solid waste (MSW). This is especially the case in secondary cities and small towns, which often face a lack of resources and know-how. Because the waste stream in these cities is usually high in organic content (50–80%) and recyclable materials (10–20%), waste-to-resource initiatives are viable options for sustainable MSW management. Waste-to-resource initiatives that are low-cost, low-tech, decentralised and community-based offer municipalities useful solutions for managing their MSW. However, the sustainability of such solutions depends on a number of key factors, such as the separation of waste at source, the effective engagement of communities and steady and predictable sources of revenue. Using quantitative data and qualitative information derived from field experience, this paper concludes that effective partnerships between a diverse range of stakeholders must be designed and fostered in order to achieve sustainability. The paper provides an analysis of stakeholder roles for the establishment of effective partnerships in four case study cities of Matale and Ratnapura (Sri Lanka) and Kon Tum and Quy Nhon (Viet Nam), where waste-to-resource facilities have been established, and explores the resources of stakeholders and how these can be mobilised to support waste-to-resource initiatives for revenue generation and long-term sustainability.